2017
DOI: 10.1089/hum.2016.025
|View full text |Cite
|
Sign up to set email alerts
|

Redirecting T Cells to Glypican-3 with 4-1BB Zeta Chimeric Antigen Receptors Results in Th1 Polarization and Potent Antitumor Activity

Abstract: T cells engineered to express CD19-specific chimeric antigen receptors (CARs) have shown breakthrough clinical successes in patients with B-cell lymphoid malignancies. However, similar therapeutic efficacy of CAR T cells in solid tumors is yet to be achieved. In this study we systematically evaluated a series of CAR constructs targeting glypican-3 (GPC3), which is selectively expressed on several solid tumors. We compared GPC3-specific CARs that encoded CD3ζ (Gz) alone or with costimulatory domains derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 68 publications
(95 reference statements)
4
75
0
Order By: Relevance
“…Previous studies have shown that GPC3-CAR T cells efficiently eradicate liver cancer cells lines that possess a high level of GPC3 expression in vivo (13, 14). Here, we observed that GPC3-CAR T cells were less effective to kill HCC cell lines in xenografts, compared to a previous report (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that GPC3-CAR T cells efficiently eradicate liver cancer cells lines that possess a high level of GPC3 expression in vivo (13, 14). Here, we observed that GPC3-CAR T cells were less effective to kill HCC cell lines in xenografts, compared to a previous report (13).…”
Section: Discussionmentioning
confidence: 99%
“…GPC3 is, therefore, a suitable target for CAR T cell therapy. Two previous studies showed the promising activity of GPC3-CAR T cells against HCC cell lines in vivo (13, 14). However, the capacity of GPC3-CAR T cells to eliminate HCC has not been evaluated in PDX models yet.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, several studies selected GPC3 as a HCC TAA [69,84,85]. Gao H, et al and Li W, et al constructed CAR-T cells that could specifically target GPC3 on the surface of HCC cells, as the attempts to apply CAR-T cell immunotherapy for the treatment in HCC, which showed significant anti-tumor activity both in vitro and in vivo [84,85]. CAR-T cells specific for HBV envelope proteins localized to liver in mice which reduced HBV replication with transient liver damage [86].…”
Section: Chimeric Antigen Receptor-engineered T Cell Immunotherapymentioning
confidence: 99%
“…It has been shown that GPC3 is expressed on the majority of hepatocellular carcinoma (HCC) and hepatoblatsoma cases but not or to a lower degree on normal liver tissue [51, 57, 67, 84]. Interestingly, GPC3 expression could be used as an HCC precancerous marker in cirrhotic livers since it is associated with dysplasia in cirrhotic livers [74].…”
Section: Introductionmentioning
confidence: 99%